Lesbian mothers' bids for normalcy in their children's schools - Bower, Laura A; Klecka, Cari L (The Educational Forum, 2009)
Albeit growing in number, lesbian mothers and their children remain a statistical minority in schools. Lesbian mothers in this study described their families as “normal” or “just like any other family.” From the perspective of queer theory, normal is a socially constructed and insidious concept. This study analyzes both the strategies participants used to be recognized as normal in their children’s schools and the reasons such recognition was perceived to be important by participants. © 2009 Taylor & Francis Group, LLC.
Keywords: dept.cur